Reactions of Simple Indoles with o-Phthaldialdehyde: Part I Synthesis of New 11-(3-Indolyl)benzo[b]carbazoles - Mardi Santoso (Jurnal Matematika & Sains, 2000)
New 11-(3-indolyl)benzo[b]carbazoles (11 and 13) can be synthesised readily in good yields from the reaction of simple indoles (8, 12) and o-phthaldialdehid (7) in the presence of phosphoryl chloride.